2016
DOI: 10.1177/0049475515621644
|View full text |Cite
|
Sign up to set email alerts
|

Female sexual dysfunction in female genital mutilation

Abstract: Female genital mutilation (FGM), otherwise known as female genital cutting (FGC), is currently very topical and has become a significant global political issue. The impact of FGM on the lives of women and girls is enormous, as it often affects both their psychology and physical being. Among the complications that are often under-reported and not always acknowledged is female sexual dysfunction (FSD). FSD presents with a complex of symptoms including lack of libido, arousability and orgasm. This often occurs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Women are affected by FGM/C in at least 28 African countries [48,49], with some also affected in the Middle Eastern and Southeast Asian countries of Yemen, Iraq, Indonesia, and Malaysia [13]. Every year, over 2 million girls experience FGM/C; in several countries such as Egypt, Eritrea, Guinea, Somalia, Mali, and Sierra Leone, over 90% of women have undergone FGM/C [50].…”
Section: Discussionmentioning
confidence: 99%
“…Women are affected by FGM/C in at least 28 African countries [48,49], with some also affected in the Middle Eastern and Southeast Asian countries of Yemen, Iraq, Indonesia, and Malaysia [13]. Every year, over 2 million girls experience FGM/C; in several countries such as Egypt, Eritrea, Guinea, Somalia, Mali, and Sierra Leone, over 90% of women have undergone FGM/C [50].…”
Section: Discussionmentioning
confidence: 99%
“…In settings where a separate psychological evaluation with a mental health expert is not feasible, standardized outpatient screening or diagnostic instruments can be used. Several studies have also shown an association between FGM/C and sexual dysfunction, 19,21–24 so screening for female sexual dysfunction may be warranted.…”
Section: The Physical Examinationmentioning
confidence: 99%
“…From a sexual medicine perspective, women who suffered FGM/C often show a burden of short- and long-term gynecological and obstetric impairments, including urinary retention, genital scarring, infections, bacterial vaginosis, perinatal complications and menstrual difficulties [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Relatedly, FGM/C is also associated with sexual function impairments [ 10 , 14 ].…”
Section: Introductionmentioning
confidence: 99%